Design and Construction of an Automatic Warm Water Media Shower Based on Arduino Uno - Fandi Ahmad; Ratnasari Ratnasari; Nur Aminudin; Ferly Ardhy; Panji Bintoro; Adamu Abubakar Muhammad (CV. Media Inti Teknologi, 2024)
This research aims to design and develop a prototype of an automatic warm water shower using sound sensors and ultrasonic sensors based on Arduino Uno. The research method uses steps from the Research and Development (R & D) Approach. The automatic warm water shower prototype developed allows users to carry out bathing activities more efficiently and comfortably, avoids wasting water due to negligence in closing the tap, and provides an automatic warm water feature. How the automatic warm water shower prototype works using a sound sensor and an ultrasonic sensor based on Arduino Uno. If the ultrasonic sensor detects the presence of an object within a distance of 30 cm, the ultrasonic sensor will activate the solenoid valve which acts as an automatic tap in turning on the tap, but when the ultrasonic sensor does not detect any the presence of an object, the ultrasonic sensor will deactivate the solenoid valve so that the tap will close automatically. If the user wants to take a shower using warm water, the user simply claps his hands and then the sound of the clapping activates the sound sensor, then the sound sensor will activate the water heater which functions as a heater. This research produces prototypes of automatic faucets and automatic hot water showers which show the potential for integrating technology into everyday bathing devices to increase user efficiency and comfort and avoid wasting water.